Seasonal distribution of soil mycoflora in Mattavara state forest of Chikkamagalur, Karnataka, India. - CHANDINI K.C,; RAJESHWARI .N, (International Journal of Pharma and Bio Sciences, 2018)
The soil fungi is an interesting group of organism which plays a major role in the ecosystem as primary decomposer in nutrient cycling whose diversity in a particular region depends upon the different climatic factors. Tropical forests are the dwelling place of greatest microbial activity. Unexplored soil of Mattavara forest was selected as study area situated between 120 54’ 42” and 13 53’53” north latitude and between 75 04’46” and 76 21’50” east latitude and is located in Chikkmagaluru district known as gate way of Western Ghats of Karnataka. Studies were conducted during different seasons from the year 2013 - 2014 to investigate the effect of physicochemical parameters to the seasonal distribution of soil fungi. Soil samples were collected out at the depth of 0 – 15 cm from triplicate sites in three different season’s rainy (July), winter (November) and summer (April) by random sampling technique. The soil fungi were enumerated by using serial dilution method on PDA media supplemented with tetracycline. A total of 39 genera and 102 species were isolated from the study area. Out of these 40 and 29 species in winter, 39 and 26 species in summer and 37 and 19 species in rainy season and classes Deuteromycotina with highest percentage followed by Zygomycotina, Ascomycotina, Oomycotina and Chytridomycetes were recorded. Total number of colonies recorded during different seasons showed variations. More number of colonies and species isolated in winter followed by summer and rainy season showed deviation from the earlier reports may be due to change in the seasonal fluctuation and all the climatic factors responsible for the seasonal variation of fungal diversity in the study area.